Characterisation of corrosion products formed on copper exposed at indoor and outdoor sites with high H2S concentrations. (1st September 2013) - Watanabe, M; Takaya, M; Handa, T; Sakai, J
<x xml:space="preserve">Abstract</x> Corrosion products formed on copper exposed indoors and outdoors at sites with high hydrogen sulphide (H2S) concentrations were characterised using several analytical techniques. The crystalline corrosion products that formed on the copper exposed indoors were chalcocite (Cu2S) and cuprite (Cu2O), while those that formed on the copper exposed outdoors were chalcocite, cuprite and basic copper sulphates. Surface analysis by X-ray photoelectron spectroscopy revealed differences between the copper exposed indoors and outdoors that are explained by the composition, localisation and oxidation of the corrosion products. The surface morphologies of the corrosion products also differed. Elemental depth profiling by glow discharge optical emission spectroscopy revealed that the corrosion products that formed indoors were mainly chalcocite with cuprite only at and near the surface. In contrast, the corrosion products that formed outdoors were a mixture of chalcocite and cuprite. These differences in corrosion products are attributed to the differences in relative humidity during exposure.